2014
DOI: 10.1136/acupmed-2013-010352
|View full text |Cite
|
Sign up to set email alerts
|

On Dermatomes, Meridians and Points: Results of a Quasiexperimental Study

Abstract: A TDE/VDE ratio of 3 : 1 implies that the clinical indications for the points of any dermatome on the torso are similar, regardless of their meridians, and suggests that most of the indications for trunk points involve a 'horizontal pattern' due to their neurobiological nature. These findings may help in understanding acupuncture's neurobiology and clarify some confusing results of clinical research, for example, excluding sham acupuncture as an inert intervention for future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Cheng [ 21 ] suggested that in ‘many cases’ the acupoints have a neuroanatomical relationship to Western medicine. Sánchez-Araujo et al [ 22 ] proposed a distinction between a ‘meridian-derived’ and a ‘neurobiology-derived’ effects depending on whether the therapeutic effects of acupoints were related to the corresponding zangfu [internal organs] or dermatome, respectively. These authors performed a partial literature compilation and found that acupoints effects for any dermatome are remarkably similar regardless of their corresponding channel [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng [ 21 ] suggested that in ‘many cases’ the acupoints have a neuroanatomical relationship to Western medicine. Sánchez-Araujo et al [ 22 ] proposed a distinction between a ‘meridian-derived’ and a ‘neurobiology-derived’ effects depending on whether the therapeutic effects of acupoints were related to the corresponding zangfu [internal organs] or dermatome, respectively. These authors performed a partial literature compilation and found that acupoints effects for any dermatome are remarkably similar regardless of their corresponding channel [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez-Araujo et al [ 22 ] proposed a distinction between a ‘meridian-derived’ and a ‘neurobiology-derived’ effects depending on whether the therapeutic effects of acupoints were related to the corresponding zangfu [internal organs] or dermatome, respectively. These authors performed a partial literature compilation and found that acupoints effects for any dermatome are remarkably similar regardless of their corresponding channel [ 22 ]. Recently, Silva [ 23 ] suggested minor corrections to the optimal dermatomes of shu acupoints to stimulate the internal organ function.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction is known as cutivisceral reflex (Wancura‐Kampik & Fanghänel, 2009) and can be used in therapeutic approaches. It has been shown that placing acupuncture needles in corresponding dermatomes achieves the best results in treating visceral organs, irrespective of their meridian attribution (Sanchez‐Araujo & Luckert‐Barela, 2014). Moreover, visceral disorders can show superficial neurogenic inflammation spots associated to acupuncture points which are located in corresponding dermatomes (Kim et al., 2017).…”
Section: Introductionmentioning
confidence: 99%